Letter from Svante Arrhenius to Georg Bredig, September 1908 - Arrhenius, Svante (1908)
Letter in which Svante Arrhenius (1859-1927) writes to Georg Bredig (1868-1944) to discuss his recent travel plans, Wilhelm Ostwald (1853-1932), and his thoughts on colloidal chemistry.
Keywords: Ostwald, Wilhelm, 1853-1932; Arrhenius, Svante, 1859-1927; Svedberg, Theodor, 1884-1971; Einstein, Albert, 1879-1955; Brownian movements; Colloids; Chemists; Nobel Prize winners; Bredig, Georg, 1868-1944